KEY TRENDS SHAPING URBAN AGGLOMERATIONS - , Т. Н., А. Н., В. Т. (Municipal economy of cities. Series: «Economy science», 2013)
The processes affecting the development of large cities. The main directions of formation of urban agglomerations.